Analisis Strategi Pemerintah Desa Dalam Pencapaian Sustainable Development Goals (Sdgs) Desa Di Kecamatan Rupat - Aryani; Sri Wahyuni, Endang (P3M Politeknik Negeri Bengkalis, 2024)
This study analyzes village government strategies in achieving the Sustainable Development Goals (SDGs) in Rupat District, focusing on villages Teluk Lecah and Pancur Jaya. The aim of this research is to evaluate the adjustment of programs, strategies, challenges, and recommendations for these villages in achieving the SDGs. The method used is qualitative with data collection techniques through observation, interviews, and documentation. The results show that the strategies implemented by the village government include infrastructure improvement, local economic development, and social programs. However, this implementation of these strategies still faces various challenges, such as limitations in human resources (HR) and finances, as well as a lack of coordination and community participation. The recommendations proposed include enhancing HR capacity, strengthening coordination between governments, increasing community participation, allocating adequate budgets, and systematic monitoring and evaluation. This research provides a comprehensive overview of the efforts, challenges, and strategies that need to be considered by the village government in Rupat District in achieving sustainable development goals.